Construction of watershed ecological security patterns with integrated of spatial variability: A case study of the Yellow River Basin, China - Bingbing Zhang; Jianrong Cao; Dengshuai Chen; Xin Li; Yanjun Liu; Jingbo Wang; Teng Liu (Ecological Indicators, 2024)
Safeguarding ecological security is one of China's important development strategies. Identifying ecological security patterns (ESPs) is an effective way to collaboratively develop ecological and environmental security in different regions. Currently, studies on the construction of regional ESPs mainly focus on the innovation of ecosystem service functions, ignoring the differences in ecological sensitivities of different ecological environments on a large scale. In this paper, taking the Yellow River Basin (YRB) as an example, six important ecosystem service functions were selected to identify ecological sources (ESs), ecological sensitivity weights were set according to the ecological environment characteristics of different regions, and the ecological resistance surfaces (ERSs) were determined. And the ESPs of the YRB were further investigated based on the Minimum Cumulative Resistance (MCR) model and circuit theory. The research findings indicate:(1) We had identified 218 ESs on the YRB, covering an area of 387,165 km2, which was 19.36 % of the entire study area and highly concentrated in the upstream areas. There were 532 ecological corridors (ECs) identified with a total length of 39,015.95 km, with less distribution in the lower reaches of the YRB. There were 201 ecological pinch points (EPPs) mainly in forests and grasslands. (2) ERSs constructed with different sensitivities weights had a significant impact on the distribution of ECs and EPPs. There were significant variations in the ESPs of the YRB. The upstream areas were notably more secure than the middle and lower reaches, indicating an overall lower level of ecological security. (3) Different ecological sensitivity weights were adopted in different regions, which was more suitable for the construction of ESPs with regional environmental differences. This study provides a wise direction for coordinating the ecological protection and achieving high-quality development in the YRB.